2018
DOI: 10.1039/c7nj04034b
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dy3+ → Sm3+ energy transfer in the tuning of warm to cold white light emission in Dy3+/Sm3+ co-doped Lu3Ga5O12 nano-garnets

Abstract: Nano-crystalline lutetium gallium garnets co-doped with Dy3+ and Sm3+ ions have been synthesized via a sol–gel method and their structural, morphological and luminescence properties have been characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…(6), it is found that the critical distance R C equals 14.809 Å in CLSO:0.20Dy 3+ /0.20Sm 3+ phosphors. And similar values are found in other systems 27,30 . Therefore, when distance between rare earth ions R < 6 Å, there exchange interaction dominants in energy transfer processes 31 while quadrupole-quadrupole interaction contributes to those processes when 6 Å < R < 14.809 Å in CLSO:0.20Dy 3+ /0.20Sm 3+ phosphor.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…(6), it is found that the critical distance R C equals 14.809 Å in CLSO:0.20Dy 3+ /0.20Sm 3+ phosphors. And similar values are found in other systems 27,30 . Therefore, when distance between rare earth ions R < 6 Å, there exchange interaction dominants in energy transfer processes 31 while quadrupole-quadrupole interaction contributes to those processes when 6 Å < R < 14.809 Å in CLSO:0.20Dy 3+ /0.20Sm 3+ phosphor.…”
Section: Resultssupporting
confidence: 89%
“…5(B). It can be found that when n value takes 10, the value of linear fitting coefficient R 2 is biggest and linear behavior is best, therefore it reveals Dy 3+ → Sm 3+ energy transfer via quadrupole-quadrupole interaction mechanism, which is consistent with others’ previous investigation 27 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…At the nanoscale, the literature is scarcer and mainly reports nanophosphors doped with trivalent lanthanide ions (Gd 3+ , Eu 3+ , Sm 3+ , Dy 3+ , Tb 3+ ), exhibiting electronic intraconfigurational transitions in the red range. Such ions are incorporated as dopant or co-dopant in the garnet-type nanophosphors and provide red emission components (Figure 2; Potdevin et al, 2005;Li and Shen, 2012;Yan et al, 2012;Haritha et al, 2014;Pamuluri et al, 2018;Ali and Khedr, 2019).…”
Section: Garnet-type Nanophosphors Doped With Other Ln 3+ Ionsmentioning
confidence: 99%
“…Rare earth oxides (RE 2 O 3 ), garnets (RE 3 A 2 B 3 O 12 , in which A and B are tetrahedral and octahedral coordinates in metal sites, respectively), oxysulfides (RE 2 O 2 S) and oxysulfates (RE 2 O 2 SO 4 ) are excellent host materials based on their optical properties. [9][10][11][12][13][14][15][16][17][18][19][20] In particular, gadolinium oxysulfate/oxysulfide (Gd 2 O 2 SO 4 /Gd 2 O 2 S) doped with Tb 3+ and Eu 3+ have revealed outstanding optical properties. Ln 2 O 2 S hosts have been used as ligand matrices for ligand to metal charge transfer (LMCT) and 4f states of lanthanides have contributed to optical processes.…”
Section: Introductionmentioning
confidence: 99%